Gender Dysphoria By The Main Character In Ray Stoeve’s Novel “Between Perfect and Real” - Putri, I Gusti Ayu Vina Widiadnya; Juniartha, I Wayan; Dewi, Sang Ayu Kadek Pitria (e-Journal of Linguistics; Vol 18 No 1 (2024): ejl-JanuaryDO - 10.24843/e-jl.2024.v18.i01.p06, 2023)
The objective of this study is to conduct an analysis of the gender dysphoria experienced by the primary protagonist as shown in the literary work titled Between Perfect and Real. The data was extracted from a literary work titled "Between Perfect and Real," encompassing both monologues and dialogues. The intention of this study is to examine the features of gender dysphoria expressed by the primary protagonist, "Dean Foster." The research employs a descriptive-qualitative approach to examine and interpret the collected data. The findings of the research are presented using both formal and informal approaches. The library research method serves as a systematic approach for gathering data. This study employs two primary theoretical frameworks to assess the collected data. The examination of the main character's gender dysphoria in the novel "Between Perfect and Real" primarily relies on the Diagnostic and Statistical Manual of Mental Disorders (DSM-5), which was introduced by the American Psychiatric Association in 2013. The Method of Characterization, as described by Kenny (1966), The second significant theoretical framework employed to analyze the depiction of gender dysphoria in the protagonist of the literary work titled "Between Perfect and Real" is applied. In the present investigation, a dataset including 50 observations was gathered, focusing on the many aspects associated with gender dysphoria as experienced by the primary protagonist.